Does the Innovative City Pilot Policy Improve Urban Resilience? Evidence from China - Mandi Tian; Zuoren Sun (Sustainability, 2024)
The assessment of the relationship between the innovative city pilot policy (ICPP) and urban resilience is crucial for enhancing cities’ ability to foresee, endure, and recover from various disruptive events. Despite the widespread implementation of the ICPP in China, it remains uncertain if this strategy will contribute to the development of urban resilience. Starting with data collected from 245 prefecture-level cities in China from 2004 to 2020, this paper initially evaluates the causal effect of the policy intervention using the difference-in-differences (DID) model and the propensity score matching-difference-in-differences (PSM-DID) method. A multi-dimensional urban resilience measurement index and a mediating effect model were constructed. The empirical results show that (1) the ICPP has a significant effect on urban resilience, which remains in force after a series of robustness tests, such as a placebo test and difference-in-differences machine learning (DML) approach; (2) regional R&D investment, technological talent attraction, green innovation capability enhancement, and information infrastructure development are identified as the mediating variable for the ICPP’s impact on urban resilience dimensions; and (3) heterogeneity study results show that the ICPP has a significantly greater impact on medium-sized cities, attributed to their capacity to enhance the resilience of cities with more growing space. Furthermore, cities with lower economic agglomeration saw a greater increase in urban resilience due to the ICPP. Accordingly, it is recommended to prioritize the allocation of innovative resources to non-coastal regions, cities with low economic agglomeration, and medium-sized cities. This study provides crucial recommendations for the enlargement of the ICPP’s scale and coordinated progress of China’s urban resilience.